HUBUNGAN KECERDASAN EMOSIONAL DENGAN STRES KERJA KARYAWAN PT. INDUSTRI KAPAL INDONESIA (PERSERO) MAKASSAR - Muhammad Akhsan Tenrisau (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2011)
This research aimed to (1) describe the emotional intellegence of PT IKI (Persero) Makassar’s employees, (2) describe the level of work stress of PT. IKI (Persero) Makassar’s employees had, and (3) seek relations between emotional intellegence and work stress of the PT. IKI (Persero) Makassar’s employees. The research employed quantitative type of research. Subject of this research was 60 employees of direct production unit of PT. IKI (Persero) Makassar. Sampling technique used was purposive random sampling. Instrument which was used as a data compiler was emotional intellegence scale and work stress scale. The research data analysed by using simple regression analyze. Result of research indicated that (1) the level of emotional Intellegence of PT. IKI (Persero) Makassar’s employees in general, was in high level. This matter depicted that components in emotional intelligence such as self awareness, self arrangement, empathy, motivation and social skill had been owned by employees. These components applicable to minimize the amount of work stress. (2) Work stress at PT. IKI (Persero) Makassar in general was at low level. Reasonal explanation for this is that there was existence of perception among workers assuming that work stressors in their job environment were not actually stressor, but challenges to finish their work demands. (3) There was a negative relation between emotional intellegence and work stress at PT. IKI (Persero) Makassar